PENGEMBANGAN MEDIA LUTAS (LUDO TATA SURYA) DALAM MUATAN IPAS UNTUK MENINGKATKAN PEMAHAMAN PESERTA DIDIK KELAS VI SEKOLAH DASAR - Tussadiyah, Halimah; Arini, Novanita Whindi (Universitas Tanjungpura, 2026)
This study aims to develop the PAPAN LUTAS learning media to improve sixth-grade elementary school students' mastery of solar system material. The method used is R&D with the ADDIE model. This media is designed to be flexible, usable anytime and anywhere as a science learning aid. Validation results showed a very high level of suitability: 91% from media experts, 80% from subject matter experts, and 92% from educational experts, with an average of 88%. Student feedback was also very positive, with scores of 96% (small-scale trial) and 99% (large-scale trial), averaging 96%. The use of the LUTAS BOARD improved students' understanding, from a pre-test score of 50% to a post-test score of 83%, an increase of 33%. Thus, the LUTAS BOARD has proven to be effective and highly suitable for science education in elementary schools..